2004
DOI: 10.1016/j.jcrs.2004.02.082
|View full text |Cite
|
Sign up to set email alerts
|

Phakic intraocular lens implantation versus clear lens extraction in highly myopic eyes of 30- to 50-year-old patients

Abstract: Implantation of a phakic IOL in a highly myopic eye of a patient between 30 and 50 years of age can be considered an adequate technique with a lower risk for loss of BCVA than CLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 9 publications
1
33
0
2
Order By: Relevance
“…One report showed that the risk of retinal detachment in pIOL cases was lower than in clear lens extraction cases. 15 Although there were no cases of retinal detachment or endophthalmitis, however, the number of subjects studied was too low to adequately detect a retinal detachment or endophthalmitis.…”
Section: Discussionmentioning
confidence: 95%
“…One report showed that the risk of retinal detachment in pIOL cases was lower than in clear lens extraction cases. 15 Although there were no cases of retinal detachment or endophthalmitis, however, the number of subjects studied was too low to adequately detect a retinal detachment or endophthalmitis.…”
Section: Discussionmentioning
confidence: 95%
“…More recently angle-supported phakic IOLs have been banned from clinical use in France. Clear lens extraction and implantation of an IOL for the correction of high myopia was performed in the 1950s by Strampelli and Barraquer and is another treatment option [27]. Colin et al [28] performed a 7-year prospective follow-up study of 52 eyes with myopia >12 D that underwent clear lens extraction.…”
Section: Discussionmentioning
confidence: 99%
“…It can be hypothesized that implantation of phakic IOLs in patients in their 40s or 50s may increase the trend to develop cataracts earlier than in nonmyopic eyes. 53 The increasing incidence of phakic intraocular procedures warrants education regarding management and prevention of potential complications. It may be advisable to perform …”
Section: Discussionmentioning
confidence: 99%